Food safety of plant origin food - Győri, Zoltán (Acta Agraria Debreceniensis, 2012)
Expectation regarding changes related to food production, transportation, distribution and marketing have changed considerably in several regions of the world over the past decades. It is especially true for highly industrialized countries where not only the food security is important but the food safety is essential too. The concentration of production – processing – distribution involves the danger on the one hand products of unsuitable quality from point of view of nutritional physiology and the other hand ones that may contain substances harmful to human health will become widespread among consumers. We investigated the heavy metal, pesticide remains and mycotoxin content of different plant products.